Implementing a Mentally Healthy Schools Framework based on the population wide Act-Belong-Commit mental health promotion campaign: A process evaluation. Issue 6 (3rd October 2016) - Anwar-McHenry, Julia; Donovan, Robert John; Nicholas, Amberlee; Kerrigan, Simone; Francas, Stephanie; Phan, Tina
Abstract : Purpose: Mentally Healthy WA developed and implemented the Mentally Healthy Schools Framework in 2010 in response to demand from schools wanting to promote the community-based Act-Belong-Commit mental health promotion message within a school setting. Schools are an important setting for mental health promotion, therefore, the Framework encourages schools to adopt a whole-of-school approach to mental health promotion based on the World Health Organisation's Health Promoting Schools framework. The paper aims to discuss these issues. Design/methodology/approach: A process evaluation was conducted consisting of six-monthly activity reports from 13 participating Western Australian schools. Semi-structured interviews were also conducted with key school contacts in November 2011 with nine schools who had signed partner agreements prior to July 2011. Findings: The schools valued promoting the mentally healthy message and the majority felt the programme was implemented successfully. More intensive implementation was facilitated by a proactive and enthusiastic school "champion" who had influence over other staff, and who did not have too many competing priorities. Factors inhibiting implementation included a lack of effective time management, lack of whole school commitment, and evaluation demands. Originality/value: Act-Belong-Commit is a positive, proactive message making it easier for teachers to talk about mental health with their students. For schools reporting implementation success, the Mentally Healthy Schools Framework raised the profile of mental health in the school setting and fostered a sense of belonging among students.